Virtual assistant for monitoring health indicators - Khavrenko Anna (онлайн, 2020)
This article briefly discusses what preventive medicine is and the basic problems of medicine nowadays. After analyzing all the problems, a solution has been found to help people take better care of their health through information technology in general and echo-devices apart. Also analyzed the main customer segments, key competitors and cited UML diagrams.
Keywords: Healthcare, Preventive Medicine, Echo Device